Predicting the diameter of as-cast D-shaped bar produced by the near shape casting technique - 221122 Dody Prayitno; Esah Hamzah; Mohd. Zulkifli Mohd. Ghazali, Tan Sri Prof. Ir. Dr., 1951-; Malaysian Science and Technology Congress (2000 : Genting Highlands, Pahang) (Skudai : Universiti Teknologi Malaysia, 2000)
22